Western approaches to Eastern Europe - J. F. Brown, Robert D. Hormats, William H. Luers ; edited by Ivo John Lederer. (Council on Foreign Relations Press)
Rev. papers from a symposium on "The United States and Eastern Europe" held in New York, Sept. 10-11, 1991. Includes bibliographical references, p. 14-15.